Dropout rate from a community-based health insurance scheme and associated factors in the Hagere Mariam district: a mixed method study - Teklemariam, Taye Anbessie; Mohammed, Fitsum Zekarias; Bogale, Getahun Gebre; Urgie, Besufekad Mulugeta; Beshah, Solomon Hailemeskel (Frontiers in Public Health, 2025)
BackgroundCommunity-based health insurance scheme is an effective strategy to accelerate the progress towards universal health coverage. This scheme plays a crucial role in reducing out-of-pocket expenses for individuals and households, thereby lowering the risk of catastrophic financial consequences. However, high dropout rates, particularly in low-and middle-income countries, continue to pose significant challenges to the successful implementation and continuation of the program. Therefore, understanding the factors contributing to scheme attrition is essential for developing targeted retention strategies and ensuring program effectiveness. Accordingly, this study assessed the dropout rate and associated factors in the Hagere Mariam district, North Shewa, Amhara Region, Ethiopia, in 2024.MethodsA cross-sectional mixed-method study was conducted to assess community-based health insurance dropout rate and associated factors in the Hagere Mariam district between February 1 and 29, 2024. The quantitative arm involved 634 systematically selected households in the Hagere Mariam district, selected through multistage sampling. The statistical analysis involved a binary logistic regression model, with the community-based health insurance membership status as the dichotomous outcome variable. After initial bi-variable screening (p < 0.25), significant variables underwent multivariable analysis, with statistical significance set at p < 0.05. The qualitative component employed purposive sampling of 10 key informants and two groups of former community-based health insurance members. The data were then thematically analyzed, and the results were triangulated with the quantitative findings.ResultsThe dropout rate from the community-based health insurance scheme among households in the Hagere Mariam district was 19.6% (95% CI = 16.42–22.9%). The poor quality of services (AOR = 7.25; 95% CI: 4.48–11.75), consistent unavailability of prescribed medications (AOR = 2.79; 95% CI: 1.29–6.05), unreimbursed out-of-pocket expenses (AOR = 3.09; 95% CI: 1.19–7.99), and absence of a chronically ill family member in the household (AOR = 3.21; 95% CI: 1.62–6.35) were the factors significantly associated with membership discontinuation.ConclusionIn the Hagere Mariam district, the dropout rate from the community-based health insurance scheme was significantly higher than the zonal average for the same year. Enhancing service quality through provider training and supervision, ensuring consistent availability of essential medicines, and reforming reimbursement policies to better protect members from financial burdens could significantly improve member retention.